Regional Specialization and Regional Leakages as an Impact of Center-Hinterland Interaction (Case: Kupang City and Regencies in West Timor) - Klau, Anggelina Delviana; Taena, Werenfridus; Kase, Marce Sherly; Blegur, Fried Markus Allung; Afoan, Felisisma (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2024)
The research aims to analyze: (1) the basic sector and regional specialization of regencies/cities in West Timor, (2) the impact of center and hinterland interactions on regional leakage in regencies/cities in West Timor. The research was carried out in 5 regencies and 1 city in West Timor. The research uses secondary data and primary data (obtained using the snowball technique). The research results state that interactions occur due to the existence of basic commodities, but not necessarily regional specialization. The research results also found that there was a leak from the Hinterland area to the center in West Timor of IDR 757,606,232,- because the benefit center was IDR 1,164,004,961,- while the hinterland benefit was IDR 406,398,729,-. Belu Regency is the regency that received a surplus (IDR 44,746,514). Therefore, each district/city is obliged to determine base commodities and strive for specialization so as to obtain a surplus from center-hinterland interactions.